OPTIMALISASI MESIN PEMARUT KELAPA UNTUK INDUSTRI RUMAH TANGGA - , ALMADORA ANWAR SANI, Dr. Ir. Subarmono, M.T., PE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study focuses on construction of coconut grater machine. The purpose of this study is to make coconut grater machine simpler, affordable for home industry, easy to operate and maintain, able to work effectively, economically, and comfortably. Knowing the grated coconut in terms of capacity and quality of product. The coconut grater machine was tested using four models of grater. First model, type A (flat) with a distance of blade is 10 mm. Second model, type B (flat) with a distance of blade is 5 mm. Third model, type C (convex) with a distance of blade is 10 mm. Fourth model, type D (convex) with a distance of blade is 5 mm. Gap distance of grater is 10 mm, 5 mm and 2 mm, each gap of grater performed three trial times. The parameters studied were the time adjusted to grate a coconut, weight, and quality of grated coconut. Results showed that the coconut grater machine is capable to grate the coconut with a capacity of 60-120 coconut/hour. Coconut grater machine is suitable for home industry with electric motor of 0.25 HP. The coconut grater machine is capable of grating coconut with good quality, especially on the grater blade flat model with distance of 5 mm and gap grater 2 mm. Coconut meat can be grated by an average of 92%. The coconut grater machine consists of five main parts: framework, electric motor, grater, receptacle, and casing. The coconut grater machine has advantage of easy to operate, movable, safe, comfortable and easy in maintenance.